2021
DOI: 10.4317/jced.58330
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and white spot lesions preventive effect of an orthodontic resin modified with silver-nanoparticles

Abstract: Background To evaluate the antibacterial property of a modified orthodontic resin with different concentrations of silver-nanoparticles (AgNPs), and quantify its preventive effect on the formation of white spot lesions (WSLs). Material and Methods An orthodontic resin (Transbond XT) was modified with four concentrations of AgNPs (1%, 0.5%, 0.1%, and 0.05%), the orthodontic resin without AgNPs was used as control. Polymerized resin discs (n=80) were submitted to Agar dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“… 71 Considering enamel remineralization, some researchers confirmed that orthodontic resin modified by a certain concentration of AgNPs (1 wt%) prevents WSL formation more efficiently ( Figure 4 ). 72 In addition, orthodontic brackets coated with titanium oxide mixed with Ag could significantly reduce the adhesion of S. mutans and P. gingivalis , and biofilm formation. 73 , 74
Figure 4 Orthodontic resin modified by a certain concentration of AgNPs.
…”
Section: Antimicrobial Agbms Incorporated In Dental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“… 71 Considering enamel remineralization, some researchers confirmed that orthodontic resin modified by a certain concentration of AgNPs (1 wt%) prevents WSL formation more efficiently ( Figure 4 ). 72 In addition, orthodontic brackets coated with titanium oxide mixed with Ag could significantly reduce the adhesion of S. mutans and P. gingivalis , and biofilm formation. 73 , 74
Figure 4 Orthodontic resin modified by a certain concentration of AgNPs.
…”
Section: Antimicrobial Agbms Incorporated In Dental Materialsmentioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. 72 …”
Section: Antimicrobial Agbms Incorporated In Dental Materialsmentioning
confidence: 99%
“…The use of AgNPs have been extensive employed in the dental field ( 24 , 25 ). Concentrations close to 1% show important antibacterial effects without affecting the mechanical properties of dental materials ( 13 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of AgNPs have been extensive employed in the dental field ( 24 , 25 ). Concentrations close to 1% show important antibacterial effects without affecting the mechanical properties of dental materials ( 13 , 25 ). The incorporation of higher concentrations of AgNPs produces color change in the material, causing it to acquire a dark grey color, affecting the esthetic characteristics of the material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation